Pengaruh Work Life Balance Terhadap Kepuasan Kerja Pada Aparatur Sipil Negara (ASN) di Lingkungan Kantor Pusat Badan Kepegawaian Negara (BKN) - H, Hidayatullah; Aprilyani, Ratnasartika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This studi aims to determine the effect of work life balance on job satisfaction in the Government Employee (ASN) within the head office of the Badan Kepegawaian Negara (BKN). This research approach used is quantitative with a population of Government Employee (ASN) employees within the head office of Badan Kepegawaian Negara (BKN) of 1050 from 27 work units. The sampling technique used was simple random sampling with a sample size of 92 respondents. The scale used to measure job satisfaction in this study was adapted by Harahap (2023) and the work life balance scale adapted by Gunawan et al., (2019). The statistical analysis test used to test the hypothesis is a simple linear regression test. Based on the results of the regression test, it shows that work life balance has a significant effect on job satisfaction in the Government Employee (ASN) within the head office of the National Civil Service Agency (BKN) by 15% with a regression coefficient value of 0.604 indicating that the higher the work life balance, the more job satisfaction increases.